1985
DOI: 10.1042/bj2280211
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a saliva-interacting cell-wall protein from Streptococcus mutans serotype f by using monoclonal-antibody immunoaffinity chromatography

Abstract: A rat monoclonal antibody, LO SM2, of the immunoglobulin M class, specific for a saliva receptor (SR) from Streptococcus mutans serotype f, was able to precipitate the SR from crude cell-wall-associated antigens (WEA) of this bacteria in presence of a detergent mixture. We have then used the technique of monoclonal-antibody immunoaffinity chromatography to purify the S. mutans SR. Pure SR was obtained from a crude WEA fraction with a single chromatographic step. The active SR could be eluted from the column in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Immune sera and Fab fragments against Antigen B, but not Antigen A, inhibited the binding of S. mutans cells to sHA (Douglas and Russell, 1984b). Antigen B, which appears to be related to components subsequently named antigen I/II (Russell et al, 1980), P1 (Forester et al, 1983), PAc (Koga et al, 1990), SR (Ackermans et al, 1985b(Ackermans et al, , 1988Ogier et al, 1990), and SpaA (Abiko et al, 1989), was found to bind to a greater extent to parotid salivacoated enamel than to uncoated enamel (Russell and Rahemtulla, 1989). A correlation was found between the expression of this protein on the surface of a number of strains of mutans streptococci and adhesion to HA coated with the parotid agglutinin (Brady et al, 1992).…”
Section: Adhesins Of Mutans Streptococcimentioning
confidence: 99%
“…Immune sera and Fab fragments against Antigen B, but not Antigen A, inhibited the binding of S. mutans cells to sHA (Douglas and Russell, 1984b). Antigen B, which appears to be related to components subsequently named antigen I/II (Russell et al, 1980), P1 (Forester et al, 1983), PAc (Koga et al, 1990), SR (Ackermans et al, 1985b(Ackermans et al, , 1988Ogier et al, 1990), and SpaA (Abiko et al, 1989), was found to bind to a greater extent to parotid salivacoated enamel than to uncoated enamel (Russell and Rahemtulla, 1989). A correlation was found between the expression of this protein on the surface of a number of strains of mutans streptococci and adhesion to HA coated with the parotid agglutinin (Brady et al, 1992).…”
Section: Adhesins Of Mutans Streptococcimentioning
confidence: 99%
“…The molecular weight of the fusion peptide was consistent with the expression of all or almost all of the cloned sequence. However, a molecular weight of about 60,000 was far from 74,000, which is the molecular weight of the S. mutans 74K SR protein (2), and a true determinants on the fusion peptide synthesized in cells containing pSAD2-4 in ELISA experiments (Fig. 4).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit polyclonal antibodies and rat monoclonal antibodies raised against the S. mutans OMZ175 74K SR protein were obtained as described by Ackermans et al (1,2). Rabbit anti-S. mutans lactate dehydrogenase and anti-CWE antibodies were prepared as previously described (33,34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations